The influence of the harvester manipulator design characteristics on the working area optimal size - Lagerev A.V.; Makulina A.V.; Lagerev I.A. (Научно-технический вестник Брянского государственного университета)
The efficiency of using logging machines on a steep slope depends on many factors, including the working area of the manipulator, which can be implemented in various technological modes of operation. The geometric parameters of the implemented working area are determined by the working position of the machine in the appropriate technological mode, that is, the place of installation of the machine relative to the tree or group of trees to be harvested. Optimization of the manipulator’s working area, formed during the operation of a logging machine, is one of the most effective ways to increase its productivity. In this article, based on a previously developed mathematical model for optimizing the structural dimensions of the links of a four-link articulated hydraulic manipulator designed for spatial manipulation of the harvester head when cutting and stacking trees for further transportation to the loading area, an analysis of the influence of the main geometric and power characteristics of the harvester on the optimal size of the working area is performed.